2023
DOI: 10.3389/fmed.2023.1292446
|View full text |Cite
|
Sign up to set email alerts
|

High proportions of post-exertional malaise and orthostatic intolerance in people living with post-COVID-19 condition: the PRIME post-COVID study

Demi M. E. Pagen,
Maarten Van Herck,
Céline J. A. van Bilsen
et al.

Abstract: BackgroundExercise-based treatments can worsen/exacerbate symptoms in people who were SARS-CoV-2 positive and living with post-COVID-19 condition (PL-PCC) and who have post-exertional malaise (PEM) or orthostatic intolerance (OI). Nevertheless, PEM and OI are not routinely assessed by clinicians. We estimated PEM and OI proportions in PL-PCC, as well as in people not living with PCC (PnL-PCC) and negatives (i.e., never reported a SARS-CoV-2 positive test), and identified associated factors.MethodsParticipants … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Studies have shown that among individuals with PCC, up to 48% of female individuals and 41% of male individuals experience postexertional malaise, and 29% of female individuals and 28% of male individuals experience orthostatic intolerance. 1 The article by Tryfonos and colleagues 2 is, therefore, timely and necessary because it addresses an important topic in the debate surrounding patient acceptability and the therapeutic effects of different exercise modalities in the treatment of patients with PCC and their acute risks of developing PESE.Tryfonos et al 2 recruited 31 nonhospitalized, community-based participants with a mean (SD) symptom duration of 21.6 (9.2) months following COVID-19 illness (with 31 age-matched and sex-matched healthy controls for comparison). This previously healthy and working-age population represents an important section of society; 78% of the PCC group were employed full-time before SARS-CoV-2 infection.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that among individuals with PCC, up to 48% of female individuals and 41% of male individuals experience postexertional malaise, and 29% of female individuals and 28% of male individuals experience orthostatic intolerance. 1 The article by Tryfonos and colleagues 2 is, therefore, timely and necessary because it addresses an important topic in the debate surrounding patient acceptability and the therapeutic effects of different exercise modalities in the treatment of patients with PCC and their acute risks of developing PESE.Tryfonos et al 2 recruited 31 nonhospitalized, community-based participants with a mean (SD) symptom duration of 21.6 (9.2) months following COVID-19 illness (with 31 age-matched and sex-matched healthy controls for comparison). This previously healthy and working-age population represents an important section of society; 78% of the PCC group were employed full-time before SARS-CoV-2 infection.…”
mentioning
confidence: 99%
“…Studies have shown that among individuals with PCC, up to 48% of female individuals and 41% of male individuals experience postexertional malaise, and 29% of female individuals and 28% of male individuals experience orthostatic intolerance. 1 The article by Tryfonos and colleagues 2 is, therefore, timely and necessary because it addresses an important topic in the debate surrounding patient acceptability and the therapeutic effects of different exercise modalities in the treatment of patients with PCC and their acute risks of developing PESE.…”
mentioning
confidence: 99%